Eficacia de agentes hemostáticos utilizados en la práctica odontológica para el control de hemorragias. Revisión bibliográfica - Lara Espinoza, Kelly Michelle (2023)
Bleeding is a complication that can occur during oral surgery, so before performing any dental procedure, especially if it is surgical, the dentist must have an optimal level of knowledge about what is being faced, as well as the factors or means used to control it. The following study is descriptive, documentary and bibliographical, for its elaboration a search of 50 bibliographical reviews was carried out in the Medigraphic, Google Academic, PubMed, Dialnet, Scielo and university repositories databases on topics related to the efficacy of hemostatic agents used in dental practice. After the analysis, it was found that the most effective hemostatic agent is tranexamic acid as the most widely used and recommended hemostatic agent prior to surgical intervention, followed by the collagenbased sponge due to its cost/effectiveness and time of action. Thus concluding that the ideal hemostatic should be easy to use, highly effective, non-antigenic, totally resorbable and have a low cost. In the same way, the correct diagnosis of the patient and the compromise between efficacy, safety and cost-effectiveness must constitute the basic pillars for the correct choice of the hemostatic agent according to the case. Finally, to act immediately in the face of this type of dental emergency, a correct diagnosis, complementary examinations, provision of different hemostatic agents in the office and surgical skills of the operator are recommended